Integrating voluntary religious contributions (nadzar) into interest-free loans (qardh): A case study of BMT Maslahah, East Java, Indonesia - Syuhri, Saifuddin; Asnawi, Nur; Djalaluddin, Ahmad (Journal of Islamic Economics Lariba, 2025)
IntroductionIslamic microfinance has increasingly recognized the potential of integrating voluntary religious contributions to address operational and financial sustainability challenges. However, empirical research exploring the specific integration of voluntary vows (nadzar) within interest-free lending (qardh) remains limited.ObjectivesThis study aims to empirically examine the operational integration and socio-economic impacts of incorporating nadzar into qardh financing at Baitul Maal Wa Al Tamwil (BMT) Maslahah in East Java, Indonesia.MethodThis research employed a qualitative case study approach, collecting data through structured interviews, participant observations, and document analysis. Data were analyzed using thematic analysis to identify operational practices, borrower perceptions, financial impacts, and socio-economic outcomes.ResultsFindings indicated that integrating nadzar contributions significantly enhanced institutional financial sustainability, borrower accountability, repayment discipline, and overall stakeholder welfare. Borrowers reported increased financial stability and stronger moral obligations, while the institution benefited from improved operational transparency, liquidity, and community trust.ImplicationsThe study demonstrates that voluntary religious contributions effectively address operational sustainability concerns, improve borrower accountability, and positively impact socio-economic outcomes. These findings provide practical guidance for Islamic financial institutions seeking ethical, sustainable financial models.Originality/NoveltyThis research contributes novel empirical insights by validating the practical integration of nadzar within qardh financing, addressing a notable gap in Islamic microfinance literature. It offers a replicable model for enhancing financial sustainability and ethical integrity within Islamic finance.